2022
DOI: 10.3390/foods11142055
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical Alteration of Enzymatically Hydrolysed and Spontaneously Fermented Oat Flour and Its Impact on Pathogenic Bacteria

Abstract: Avena sativa (A. sativa) oats have recently made a comeback as suitable alternative raw materials for dairy substitutes due to their functional properties. Amylolytic and cellulolytic enzyme-assisted modifications of oats produce new products that are more appealing to consumers. However, the biochemical and functional alteration of products and extracts requires careful selection of raw materials, enzyme cocktails, and technological aspects. This study compares the biochemical composition of different A. sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Wells (Ø = 6 mm) were punched in the agar and filled with 50 µL of extracts. Agar plates were incubated at 37 • C for 24 h, and inhibition zones were measured and tabulated [37,57].…”
Section: Antibacterial Assaymentioning
confidence: 99%
“…Wells (Ø = 6 mm) were punched in the agar and filled with 50 µL of extracts. Agar plates were incubated at 37 • C for 24 h, and inhibition zones were measured and tabulated [37,57].…”
Section: Antibacterial Assaymentioning
confidence: 99%
“…The widely recognized yogurt starters, Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus , are used in the fermentation of plant-based products [ 28 , 53 , 54 ]. In different studies, these strains have been found to alleviate the symptoms associated with lactose intolerance [ 55 ], which is related to the provision of β-galactosidase (lactase), a digestive enzyme that aids in breaking down lactose [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Following EAE, the liquid phase was used for further fermentation before freezing, as previously described by Streimikyte [ 28 ]. Specifically, 10% Tibetan Kefir grains was added to the liquid samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations